Hubungan Kecerdasan Spiritual Islam Dan Kesiapan Mental Siswa Terhadap Motivasi Belajar Matematika - Ficha Andreini YZ; Muthia Sarah; Nurulzhia Rahma Nisa; Zahratul Aini Putri; M. Imamuddin (KOLONI, 2023)
Negative mindset will have an impact on students’ mentality when continuing their studies to a higher level. Basically, mathematics looks difficult only because students do not understand the basic materials. This happens due to a lack of motivation possessed by students which can be a result of low Islamic spiritual intelligence possessed by students. With good mental readiness conditions will be able to create effective learning. The research method that researchers use is the literature review method, which is a synthesis of the works of thought produced by previous researchers. Spiritual intelligence according to the Islamic perspective teaches us that seeking knowledge is obligatory for every Muslim. There are several factors that influence student learning readiness including physical conditions (mental and emotional), needs (motives and goals), skills, knowledge that has been learned. Based on the research that researchers have conducted, there is a positive and significant relationship between spiritual intelligence and readiness students’ mental motivation to learn mathematics. Keywords: Islamic Spiritual Intelligence, Students' Mental Readiness, Mathematics Learning Motivation